The impact of climate change on the resistance of rice near-isogenic lines with resistance genes against brown planthopper - Kuang, Yun-Hung; Fang, Yu-Fu; Lin, Shau-Ching; Tsai, Shin-Fu; Yang, Zhi-Wei; Li, Charng-Pei; Huang, Shou-Horng; Hechanova, Sherry Lou; Jena, Kshirod K.; Chuang, Wen-Po (Springer, 2021)
The impact of climate change on insect resistance genes is elusive. Hence, we investigated the responses of rice near-isogenic lines (NILs) that carry resistance genes against brown planthopper (BPH) under different environmental conditions. Results We tested these NILs under three environmental settings (the atmospheric temperature with corresponding carbon dioxide at the ambient, year 2050 and year 2100) based on the Intergovernmental Panel on Climate Change prediction. Comparing between different environments, two of nine NILs that carried a single BPH-resistant gene maintained their resistance under the environmental changes, whereas two of three NILs showed gene pyramiding with two maintained BPH resistance genes despite the environmental changes. In addition, two NILs (NIL-BPH17 and NIL-BPH20) were examined in their antibiosis and antixenosis effects under these environmental changes. BPH showed different responses to these two NILs, where the inhibitory effect of NIL-BPH17 on the BPH growth and development was unaffected, while NIL-BPH20 may have lost its resistance during the environmental changes. Conclusion Our results indicate that BPH resistance genes could be affected by climate change. NIL-BPH17 has a strong inhibitory effect on BPH feeding on phloem and would be unaffected by environmental changes, while NIL-BPH20 would lose its ability during the environmental changes.